Strategi Sekolah dan Implementasi Guru dalam Transformasi Pembelajaran PAI Berbasis Teknologi Digital di MAN 2 Kulonprogo - Ansorul Alim; Sibawaihi Sibawaihi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study analyzes the strategy of integrating learning technology at MAN 2 Kulonprogo in balancing technological progress and Islamic values. Using a qualitative case study method with a change management approach and the TPACK framework, the study reveals three main findings. First, institutional strategies through the institutionalization of Jogja Madrasah Digital (JMD) and teacher training successfully transformed coercive regulations into a digital cultural habituation. Second, pedagogical TPACK implementation is applied through micro-learning strategies and multimedia visualization relevant to Generation Z student psychology. Third, digital evaluation transformation functions as a character education instrument to instill values of honesty (Siddiq) and accountability (Amanah) through a transparent system. It is concluded that the madrasah successfully positions technology as a wasilah (tool) that strengthens academic integrity and student morals, rather than merely modernizing tools.